2018
DOI: 10.2134/agronj2017.08.0475
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Efficiency in Living Mulch and Annual Cover Crop Corn Production Systems

Abstract: Corn (Zea mays L.) comprises 95% of the feed grain production in the United States. The area dedicated to corn production in the southeastern United States has increased over the past decade, raising concerns about environmental degradation, and creating a need for more sustainable productions systems. One production system that addresses these concerns is the white clover (Trifolium repens L.) living mulch (LM). Previous research defined a sustainable LM system for corn production, but questions regarding wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Generally, the simulation models with wheat CC terminated chemically in early April each year suggest that wheat CC system enhanced water storage for the following summer crops in normal, wet, and dry years and that water storage for soybean growing season was better in normal year than dry and wet years (Figure 4). Sanders, Andrews, and Hill (2018) found that living CC system may be most favorable for water storage in soils with high water‐holding capacity in regions with high precipitation. In a dry year, planting a winter CC increased soil water storage for the cash crops (Dabney, Delgado, & Reeves, 2001; Daigh et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the simulation models with wheat CC terminated chemically in early April each year suggest that wheat CC system enhanced water storage for the following summer crops in normal, wet, and dry years and that water storage for soybean growing season was better in normal year than dry and wet years (Figure 4). Sanders, Andrews, and Hill (2018) found that living CC system may be most favorable for water storage in soils with high water‐holding capacity in regions with high precipitation. In a dry year, planting a winter CC increased soil water storage for the cash crops (Dabney, Delgado, & Reeves, 2001; Daigh et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These reductions have been attributed to competitive N uptake by the intercropped clover and reduced N mineralization during unfavorable environmental conditions, and can have a negative impact on overall corn growth and yield (Andrews et al 2018;Kurtz et al 1952;Liedgens et al 2004;Ochsner et al 2010). Reductions in soil moisture have also been reported in leguminous LM systems due to additional evapotranspiration by the intercropped clover, but this does not seem to dramatically affect percolation (figure 4) (Sanders et al 2018;Ochsner et al 2010;Zemenchik et al 2000). Therefore, reduced soil N is likely the main cause of reduced NO 3 -N in leguminous LM systems (Ochsner et al 2010).…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…A living mulch system (LMS) is a modified cover crop system in which a legume cover crop grows throughout the cash crop's growing season while contributing enough N to the soil pool to satisfy the needs of the cash crop (Zemenchik, Albrecht, Boerboom, & Lauer, 2000). These systems have been shown to provide a variety of benefits compared with bare soil and full cover crop suppression, including reduced erosion, nitrate leaching, and fertilizer use (as much as 75% less in some field trials), but they function best in areas with ample available water (Hartwig, Ammon, Science, Hartwig, & Ammon, 2002; Nakamoto & Tsukamoto, 2006; Ochsner, Albrecht, Schumacher, Baker, & Berkevich, 2010; Sanders, Andrews, & Hill, 2018; Zemenchik et al., 2000). Due to these benefits, the LMS is being promoted as a potential sustainable alternative to conventional row crop agriculture, but the environmental impacts are relatively unknown.…”
Section: Introductionmentioning
confidence: 99%